“Thou shalt love thy neighbor as thyself”? The relationship of self-care with empathy and altruistic behavior - Pilarska, Aleksandra; Suchańska, Anna (Przegląd Psychologiczny, 2022)
Aim The aim of the study was to investigate whether self-care, understood as a set of functions ensuring one’s own safety and personal development, promotes a tendency toward empathy and altruism. Method The study was conducted online on a group of 331 people, using the Self-Care Questionnaire, the Empathic Sensitiveness Scale, the Altruism Questionnaire, and the Social Desirability Questionnaire. The data was analyzed using both a variable-centered and a person-centered approach. Results Results obtained through path analysis revealed that the association between self-care capacity and engaging in altruistic behavior was mediated by tendencies toward empathic concern and perspective-taking. Self-care contributed to willingness to behave for the benefit of others, as it fostered other-oriented empathy. Cluster analysis results confirmed that properly developed abilities to protect and care for oneself were accompanied by empathic sensitivity to the welfare of others and willingness to engage in altruistic behavior. Notwithstanding, the results also indicated that self-care deficits do not preclude engaging in helping activities when they allow one to reduce one’s own empathic suffering. Conclusions Results obtained through correlation-regression and cluster analyses demonstrated that self‑care promotes mature empathizing – associated with empathic concern and perspective-taking – and engaging in selfless actions for the benefit of others.